High voltage - Institution of Engineering and Technology; Zhongguo dian li ke xue yan jiu yuan (The Institution of Engineering and Technology, 2016)
"The scope covers high-voltage power engineering and high voltage applications, including experimental, computational (including simulation and modelling) and theoretical studies which include: Electrical Insulation, Discharge and plasmas, pulse power, High-fields effects, High voltage engineering."
Keywords: High voltages : Periodicals; High voltages